LEGAL ANALYSIS OF LAND BANK INSTITUTIONS IN INDONESIA (Comparative Study with the United States) - Devi Febriyanti; Rehnalemken Ginting; Waluyo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study analyzes the idea and implementation of the Land Bank in Indonesia, comparing it with similar systems in other nations, especially the United States. This study aims to examine the Land Bank policy in Indonesia, juxtapose its frameworks with those in the United States, and formulate an optimal Land Bank concept suitable for implementation in Indonesia. This study employs a normative juridical methodology using comparative legal and philosophical methods. The findings indicate that although the Land Bank in Indonesia has the same aims as its counterpart in the United States, namely land management for public benefit, there are considerable disparities in operational and regulatory methodologies. In Indonesia, the Land Bank is mostly centralized and oriented towards social concerns, but in the United States, it is more decentralized and operates as a financial entity. The optimal framework for a Land Bank in Indonesia must emphasize justice, openness, and sustainability, while enhancing the function of Notary/PPAT and improving the integration of land information systems. This study underscores the significance of cooperation among the government, corporate sector, and communities to establish an efficient and sustainable Land Bank in Indonesia.